Detection of the invasive mosquito species Aedes (Stegomyia) albopictus (Diptera: Culicidae) in Portugal - Osório, Hugo (2019)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).